Bacteriological studies in the diphtheria epidemic in Buenaventura, Valle, Colombia in 1992 - Carmona, Fabio; Barona, Graciela; de Alvarez, Eunice; Astudillo, Miryam (Colombia Medica, 1993)
During 1992 (June to December), a diphtheria epidemic occurred in the port of Buenaventura, Valle, on Colombia’s Pacific coast. A total of 88 patients were detected; 51 were studied bacteriologically toxigenic C. diphtheriae was isolated in 28 (54.9%) patients; 4 (7.8%) carried nontoxigenic C. diphtheria, and in 5 (98%) nontoxigenic C. pseudodiphtheriticum was cultured from the 28 patients with toxigenic C. diphtheriae were females with ages between 11 to 15 year old. The sensibility to antibiotics was tested, and all isolates were resistant to tetracycline.